E-business capability and value among retail SMEs: Some empirical evidence from Malaysia - Amin, Mohammad Ruhul; Hussin, Husnayati; Suhaimi, Mohd Adam; Kartiwi, Mira; Mohamed Razi, Mohamed Jalaldeen (IEEE, 2017)
Electronic business (e-business) can potentially develop SME’s adeptness and efficacy in facing the fast-changing and competitive business environment. Despite the success of many larger counterparts, SMEs are still lagging behind in using the Internet for their business especially in the context of developing countries. Although it is observed that some SMEs are beginning to catch up, still many of them do not realize full benefits of e-business and face difficulties in generating e-business value. This study presents some descriptive findings related to how retail SMEs in Malaysia used the Internet and social networks to support their business. Based on useful 200 survey responses from SME owner/managers, descriptive results are discussed. The findings indicate that most Malaysia retail SMEs focused on information and transaction-based e-business capabilities rather than integration with suppliers or partners. Additionally, most perceived they gained business value as a result of their e-business engagement. The findings provide insights on e-business capability and value for the retail SMEs.